2012
DOI: 10.1094/php-2012-0523-01-br
|View full text |Cite
|
Sign up to set email alerts
|

The Pest Potential of Brown Marmorated Stink Bug on Vegetable Crops

Abstract: The brown marmorated stink bug, Halyomorpha halys (Stål) is an invasive insect in the Mid-Atlantic region that is spreading rapidly across the United States. In this article, the authors document the pest potential of this bug to vegetable crops based on their observations in the Mid-Atlantic United States thus far. Accepted for publication 20 April 2012. Published 23 May 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…The clear dominance and high abundance of BMSB nymphs (and exuviae) present and the severe feeding damage recorded in the two crops confirm the results of previous studies (e.g. 25, 29,31,32) that bean and pepper are major hosts of BMSB.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The clear dominance and high abundance of BMSB nymphs (and exuviae) present and the severe feeding damage recorded in the two crops confirm the results of previous studies (e.g. 25, 29,31,32) that bean and pepper are major hosts of BMSB.…”
Section: Discussionsupporting
confidence: 88%
“…28,29,30,31,32,33). Beans (in particular Phaseolus vulgaris L.) and peppers (Capsicum annuum L.), the plants being in the focus of our survey, have been shown to be attractive hosts of the stink bug species (23,25,29,30,31,32,33). Symptoms of damage differ according to the plant species affected, and these have been described and illustrated by Kuhar et al (29) and Rice et al (25).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…The extent of BMSB damage and risk to vegetables has not been fully determined. Based on observations and initial research from the mid-Atlantic USA region, this pest will feed on and cause severe damage to a number of vegetables when densities are high (Kuhar et al 2012). Sweet corn (Zea mays) appears to be a strongly preferred host crop, on which numerous nymphs and adults have been observed on a single ear and nearly 100% damage has been recorded in fields ( Figure 6).…”
Section: Brown Marmorated Stink Bugmentioning
confidence: 99%
“…Although no population density estimates for this pest have been found, Inkley found that more than 26,000 of these pests were collected in one home in Maryland over a period of 181 days (Inkley, 2012). Kuhlar et al found as many as 20 adult or nymph H. halys on a single ear of sweet corn (Kuhar et al, 2012). With the passing of the Food Quality and Protection Act in 1996, broadspectrum insecticides, which previously were successful in combating native stink bug populations, have been regulated such that they are not effective in controlling H. halys (Leskey et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%